Residents' Perceptions of Film-Induced Tourism - André Rafael Ferreira; Raquel Mendes; Laurentina Vareiro (European Regional Science Association (ERSA), 2015)
This study's main objective is to explore residents? perceptions of film-induced tourism and the impacts of filmmaking on the development of a destination. Specifically, the research examines residents perceptions of the social, economic, and environmental impacts on two Portuguese municipalities (Arcos de Valdevez and Estremoz) given their features in two popular Portuguese television series. Data is collected by means of an Internet survey in 2014, in which residents? perceptions of the impacts of filmmaking are solicited. Residents from the two municipalities generally agree that the recording and exhibition of the television series is important to their municipality, and contributes to the increased number of tourists. Given that residents consider that the positive impacts are more significant than the negative impacts, they supported the recording of other television series in the same municipalities. Although perceptions of residents from Arcos de Valdevez and Estremoz were similar, some significant differences were found. Considering that destination managers and tourism development authorities aim to plan for optimal tourism development, and at the same time wish to minimize the negative impacts of this development on the local communities, monitoring residents? opinions of perceived impacts is a good way of incorporating their reaction into tourism planning and development. The results of this research may provide useful information in this sense.
Keywords: L83; R58; 330; Film-induced tourism; residents' perceptions; tourism development; impacts